2010
DOI: 10.1016/j.dental.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of proanthocyanidin–dentin matrix interaction

Abstract: Objectives-To characterize the properties of dentin matrix treated with two proanthocyanidin rich cross-linking agents and their effect on dentin bonded interfaces.Methods-Sound human molars were cut into 0.5 mm thick dentin slabs, demineralized and either treated with one of two cross-linking agents (grape seed -GSE and cocoa seed -COE extracts) or left untreated. The modulus of elasticity of demineralized dentin was assessed after 10 or 60 min and the swelling ratio after 60 min treatment. Bacterial collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
3
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 27 publications
4
163
3
17
Order By: Relevance
“…20 The Proanthocyanidin have been demonstrated to increase the ultimate tensile strength and elastic modulus of demineralized dentin. 14,40 According to the results obtained in this study, it could be concluded that type I collagen fibers from human dentin or bovine Achilles deep tendon are structurally similar when evaluated by ATR-FTIR spectroscopy. The 35% phosphoric acid used for surface conditioning for a short period of time (15 s), significantly altered the organic content of amide, proline and hydroxyproline.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…20 The Proanthocyanidin have been demonstrated to increase the ultimate tensile strength and elastic modulus of demineralized dentin. 14,40 According to the results obtained in this study, it could be concluded that type I collagen fibers from human dentin or bovine Achilles deep tendon are structurally similar when evaluated by ATR-FTIR spectroscopy. The 35% phosphoric acid used for surface conditioning for a short period of time (15 s), significantly altered the organic content of amide, proline and hydroxyproline.…”
Section: Discussionmentioning
confidence: 56%
“…In this way, the acid phosphoric was applied for 15 s, necessary to etch dentin before the application of an etch-and-rinse adhesive system; the application time for distilled water and 2% chlorhexidine digluconate was 60 s, accordingly to the literature 11 ; the application time for EDTA was 60 s, accordingly to the literature 10 ; and the application time selected for the proanthocyanidin solution was 60 min, accordingly to the literature. 13,14 After the immersion time had elapsed, each collagen membrane was carefully removed with a sterile clinical forceps, which was changed for each sample. After the immersions, the membranes of groups G1 and G4 (immersed in water and 2% chlorhexidine, respectively) were only lightly dried with filter paper (Whatman No.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Maciel et al 47) , the acetone group showed lower swelling values compared to distilled water group, the probable causes of this phenomenon can be the higher ability of the acetone-saturated collagen fibrils to form interpeptide bonds and the absence of the plasticizing effect of water in the acetone group. In another study, Castellan et al reported that both GSE and COE derived PA can decrease the swelling ratio and water sorption rate of collagen matrix 45) . In this study, no statistically significant changes were occurred in UTS values of dentin matrix treated with either GSE or COE whilst both of these groups, showed a considerable difference in UTS values in comparison with the control group.…”
Section: Pa-collagen Fibers Interactionsmentioning
confidence: 95%
“…It is assumed that stiffening effect induced by crosslinkers may reduce the risk of collagen collapse after demineralization and dentin overdrying, and hence, may permit more hydrophobic adhesives to enter into interfibrilar spaces 44) . As a rule, a stiffer dentin matrix is a so more suitable collagen substrate for hybridization 45) . Bedran-russo et al demonstrated that GSE PA can increase the stiffness and ultimate tensile strength of demineralized dentin in a concentration-related and time-dependent manner 28,29) .…”
Section: Pa-collagen Fibers Interactionsmentioning
confidence: 99%